Internalization of Disciplinary Values through Reward and Punishment Approaches in Islamic Religious Education Learning at Junior High Schools: A Multisite Study in Ponorogo - Hafizh Raafi; Syarifah Syarifah; Adnun Yalipele; Hamim Abdillah (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze the internalization of disciplinary values through the reward and punishment approach in Islamic Religious Education learning at junior high schools. This research was motivated by the existence of various disciplinary problems among students, such as tardiness, lack of responsibility in completing assignments, and violations of school regulations. The research employed a qualitative descriptive approach with a multi-site study design conducted at SMP Negeri 1 Ponorogo, SMP Muhammadiyah 1 Ponorogo, and SMP Ma’arif 1 Ponorogo. Data were collected through observation, interviews, and documentation, while data analysis was carried out through data reduction, data presentation, and conclusion drawing using source and technique triangulation. The findings revealed that the implementation of reward and punishment in Islamic Religious Education learning had a positive impact on shaping students’ disciplinary character. Rewards were given in the form of praise, verbal appreciation, additional scores, and appreciation for positive behavior, while punishments were applied educatively through warnings, advice, guidance, and educational assignments. In addition, the internalization of disciplinary values was strengthened through positive habituation and teacher role modeling in daily school activities. The consistent implementation of reward and punishment was proven to improve students’ learning motivation, responsibility, and compliance with school regulations. Therefore, reward and punishment can be an effective strategy in developing students’ disciplinary character in junior high schools.